Implementation of the Katarungang Pambarangay in the Selected Barangay in Legazpi City for FY 2015-2020 - Consorcia Evelyn Sotto (Philippine Association of Institutions for Research, Inc., 2021)
The study aimed to determine the level of implementation of the Lupong Pangkapayapaan at the selected barangays in Legazpi City for FY 2015-2020. Specifically, it aimed to determine the status of Katarungang Pangbarangay in terms of the nature of complaints filed by the residents, problems encountered by the Lupong Tagapamayapa in its effort to amicably settle disputes, and propose recommendations that may be suggested by the Lupon Members and by the parties to the disputes as regards the effective settlement of disputes. The descriptive method of research was used. The study revealed that there were different disputes among the residents filed, there were problems encountered by the Lupong Tagapamayapa in its effort to settle the disputes amicably, and there were proposed recommendations with regards to the effective settlement of the disputes. As recommended, the members of the committee should have enough knowledge in handling the different disputes that are being filed in the barangay, and the barangay council should conduct a seminar on the basic laws, protocols, and procedures to provide more knowledge and skills necessary in addressing disputes in the community. The local government unit should continue to empower the members of the committee in its effort to the effective settlement of the different disputes.